MENINGKATKAN HASIL BELAJAR CIRI-CIRI BANGUN DATAR MENGGUNAKAN WORDWALL DENGAN DISCOVERY LEARNING DI SEKOLAH DASAR - Puno, Stenly M.; Abdullah, Gamar; Aries, Nur Sakinah; Marshanawiah, Andi; Kudus, Kudus (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This study was conducted to improve students’ learning outcomes on the topic of plane figure characteristics through the integration of Wordwall media and the Discovery Learning model in Grade IV of SDN 17 Limboto. The research employed a Classroom Action Research (CAR) design implemented in two cycles. The participants consisted of 20 fourth-grade students. Data were collected through classroom observations, learning achievement tests, and documentation, and analyzed descriptively based on the improvement of learning mastery in each cycle. The findings revealed that, prior to the intervention, only a small proportion of students achieved the Minimum Learning Achievement Criteria (KKTP). After the implementation of the first cycle, learning mastery increased to 75%, but had not yet met the success indicator. Further refinement of the learning process in the second cycle resulted in a substantial improvement, with 95% of students achieving mastery learning. These results indicate that discovery-based learning supported by interactive Wordwall media enhances student engagement, facilitates conceptual understanding, and leads to improved learning outcomes. Therefore, the use of the Discovery Learning model assisted by Wordwall media is considered effective for improving elementary school students’ learning outcomes on plane figure characteristics. ABSTRAKPenelitian ini dilaksanakan untuk meningkatkan hasil belajar siswa pada materi ciri-ciri bangun datar melalui penerapan media Wordwall yang dipadukan dengan model Discovery Learning di kelas IV SDN 17 Limboto. Penelitian menggunakan pendekatan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Subjek penelitian berjumlah 20 siswa kelas IV. Data dikumpulkan melalui observasi, tes hasil belajar, dan dokumentasi, kemudian dianalisis secara deskriptif berdasarkan peningkatan ketuntasan belajar pada setiap siklus. Hasil penelitian menunjukkan bahwa pada kondisi awal hanya sebagian kecil siswa yang mencapai Kriteria Ketercapaian Tujuan Pembelajaran (KKTP). Setelah penerapan tindakan pada siklus I, ketuntasan belajar meningkat menjadi 75%, namun belum memenuhi indikator keberhasilan. Perbaikan pembelajaran pada siklus II menunjukkan peningkatan yang lebih optimal, dengan ketuntasan belajar mencapai 95%. Temuan ini menunjukkan bahwa pembelajaran berbasis penemuan yang didukung oleh media Wordwall mampu meningkatkan keaktifan siswa, membantu pemahaman konsep, serta berdampak positif terhadap hasil belajar. Dengan demikian, penerapan model Discovery Learning berbantuan media Wordwall efektif digunakan untuk meningkatkan hasil belajar siswa pada materi ciri-ciri bangun datar di sekolah dasar.